Effect of Aerobika®️ Device in Sputum Induction, Pulmonary Function and Thoracic Expansion in Phase One Cardiac Rehabilitation for Post CABG Subjects: A Randomized Prospective Controlled Trial - Varun, Naik; Paramshetti , Anuradha (Nepalese Heart Journal, 2025)
Background: Patients who undergo coronary artery bypass graft (CABG) surgery frequently experience pulmonary complications shortly after the procedure due to reduced lung function and a weakened cough reflex. The recent study aimed to determine and evaluate the effects of the Aerobika®️ device on sputum induction, pulmonary function, and thoracic expansion in phase one cardiac rehabilitation for post-CABG subjects. Methods: A randomized, prospective controlled trial was conducted on 36 participants with median sternotomy. Participants were assigned to either Group A (n=18) or Group B (n=18). The session was carried out for 30 minutes twice a day for a week. Outcome measures in the present study were sputum volume, thoracic expansion measurements, peak expiratory flow meter, and maximal inspiratory pressure. The outcome measures were evaluated on a daily basis, i.e., pre- and post-every session. Statistical analysis was done using SPSS 23. The Wilcoxon test was used for within-group pre-test and post-test comparison, whereas the Mann-Whitney test was used for between-group comparison. The level of significance was set at 5%. Results: Within-group analysis indicated that both groups demonstrated statistically significant improvements in all parameters individually (p-value = 0.001< 0.05). Between-group comparison demonstrated that the experimental group was more effective in enhancing secretion clearance, thoracic expansion, maximal inspiratory pressure, and peak expiratory flow meter as evidenced by significant differences (p-value = 0.001<0.05). Conclusion: The study concluded that phase one cardiac rehabilitation, along with the use of the Aerobika®️ device, is effective in improving the sputum induction, pulmonary function, and thoracic expansion of the lung.